The Analysis Of Fiscal And Monetary Policy To Overcome The Impact Of Regional Expansion On Macroeconomic Stability In Indonesia - Ebenezer Silaban, Daniel (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to analyze the fiscal and monetary policies implemented by the Indonesian government to address the impact of regional expansion on macroeconomic stability. The method used in this research is descriptive analysis with a qualitative approach. The data used is secondary data in the form of fiscal and monetary policy documents issued by the government and Bank Indonesia. The results of the study show that the Indonesian government has implemented various fiscal and monetary policies to overcome the impact of regional expansion on macroeconomic stability, such as increasing government spending in new regions, setting interest rate policies, and controlling inflation. However, there are still a number of challenges in overcoming the impact of regional expansion, such as differences in economic conditions in new regions and a lack of adequate human resources. The effects of fiscal and monetary policies on inflation and economic growth are also analyzed in this study. The results of the analysis show that fiscal and monetary policies have a significant effect on inflation, but have not been proven to be consistent in increasing economic growth. Based on the research results, it can be concluded that the fiscal and monetary policies implemented by the Indonesian government to overcome the impact of regional expansion have made a positive contribution to macroeconomic stability. However, proper policy evaluation and adjustments are still needed to overcome the challenges that are still being faced.